Interaction of extreme ocean waves with offshore structures - Walker, D; Walker, Daniel Anthony Guy (2006)
﻿ With most of the world's untouched oil and gas resources offshore and the possibility that hurricanes are becoming more frequent and more intense, the risks associated with offshore oil and gas production are increasing. Therefore, there is an urgent need to improve current understanding of extreme ocean waves and their interaction with structures. This thesis is concerned with the modelling of extreme ocean waves and their diffraction by offshore structures, with the ultimate aim of proposing improved tools for guiding airgap design. The feasibility of using linear and second order diffraction solutions with a suitable incident wave field to predict extreme green water levels beneath multi-column structures is investigated. Such tools, when fully validated, could replace the need to carry out model tests during preliminary design. When contemplating airgap design it is crucially important that consideration is given to the largest waves in a sea state, the so-called freak or rogue waves. This thesis studies the nature of one specific freak wave for which field data is available, namely the Draupner New Year wave. Unique features of this wave are identified, distinguishing it from a typical large wave, and an estimate of the probability of occurrence of the wave is given. Furthermore, a design wave, called NewWave, is proposed as a good model for large ocean waves and is validated against field and experimental data. The diffraction of regular waves and NewWaves by a number of structural configurations is studied. In order to assess the validity of using diffraction solutions for the purposes of airgap design, comparisons are made with measured wave data from a programme of wave tank experiments. Wave data for a real platform configuration are examined to highlight the key issues complicating the validation of diffraction based design tools for real structures. The ability of diffraction theory to reproduce real wave measurements is discussed. The phenomenon of near-trapping is also investigated, allowing guidelines for airgap design to be established.